Science behind biostimulant action of seaweed extract on growth and crop yield: insights into transcriptional changes in roots of maize treated with Kappaphycus alvarezii seaweed extract under soil moisture stressed conditions - Kumar, Ranjeet; Trivedi, Khanjan; Anand, K. G. Vijay; Ghosh, Arup (Journal of applied phycology, 2020)
Seaweed extracts have been reported to be effective crop biostimulants having low carbon foot print. However, the mechanism of their action on crops has remained elusive due to dearth of studies. Kappaphycus alvarezii seaweed extract (K-sap) has been found to increase the yield of several crops as well as impart drought tolerance. Here, an attempt was made to get a global view of the transcriptome response of maize roots when subjected to soil drench application of K-sap under normally irrigated and drought conditions. mRNA were sequenced using high-throughput RNA sequencing employing Illumina platform and transcriptome mapping was carried out. K-sap applied plants under drought, when compared to its control, recorded several differentially expressed genes involved in RNA-, protein-, cell wall–, signaling-, transport-, stress-, development-, cell-, secondary metabolism–, hormone metabolism–, DNA-, lipid metabolism–, major and minor CHO metabolism–, redox-, metal handling–, amino acid metabolism–, nucleotide metabolism–, TCA-, and N metabolism–related pathways. Up-regulation was observed in the genes coding towards enhancement of root growth, gibberellic acid and auxin signaling, seed development, nitrogen metabolism, transport, and antioxidant activity like glutathione S -transferase and peroxidases. On the other hand, down-regulation of starch and sucrose degradation–related transcripts was apparent. These related well to our morphological observations on improved root growth, grain yield, and higher nutrient content of the roots under drought stress owing to application of K-sap. The study gives a comprehensive insight of several biological processes being modulated and opens up avenues for further targeted mechanistic studies.